2024
DOI: 10.3389/ijph.2024.1606913
|View full text |Cite
|
Sign up to set email alerts
|

Risk Prediction for Sudden Cardiac Death in the General Population: A Systematic Review and Meta-Analysis

Yue Li,
Zhengkun Liu,
Tao Liu
et al.

Abstract: Objective: Identification of SCD risk is important in the general population from a public health perspective. The objective is to summarize and appraise the available prediction models for the risk of SCD among the general population.Methods: Data were obtained searching six electronic databases and reporting prediction models of SCD risk in the general population. Studies with duplicate cohorts and missing information were excluded from the meta-analysis.Results: Out of 8,407 studies identified, fifteen stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Additionally, an adequate sample size enhances the model’s stability and reliability. Thus, future research should strive to ensure sufficiently large sample sizes to support model development and validation ( 60 ). Furthermore, this study found that some models were developed using single-center studies, which may limit the models’ broad applicability.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, an adequate sample size enhances the model’s stability and reliability. Thus, future research should strive to ensure sufficiently large sample sizes to support model development and validation ( 60 ). Furthermore, this study found that some models were developed using single-center studies, which may limit the models’ broad applicability.…”
Section: Discussionmentioning
confidence: 99%